2013
DOI: 10.1111/mafi.12027
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Insurance Design Under Rank‐dependent Expected Utility

Abstract: We consider an optimal insurance design problem for an individual whose preferences are dictated by the rank-dependent expected utility (RDEU) theory with a concave utility function and an inverse-S shaped probability distortion function. This type of RDEU is known to describe human behavior better than the classical expected utility. By applying the technique of quantile formulation, we solve the problem explicitly. We show that the optimal contract not only insures large losses above a deductible but also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(114 citation statements)
references
References 55 publications
0
113
0
Order By: Relevance
“…As described in Yaari [6] and Bernard et al [7], this framework fails to explain various phenomena that are observed in practice, for instance, that financial agents prefer to purchase extended insurance cover for relatively small claims over buying protection against disastrous large claims. Bernard et al [7] modify the original framework by introducing a probability distortion which tries to describe human behavior more appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…As described in Yaari [6] and Bernard et al [7], this framework fails to explain various phenomena that are observed in practice, for instance, that financial agents prefer to purchase extended insurance cover for relatively small claims over buying protection against disastrous large claims. Bernard et al [7] modify the original framework by introducing a probability distortion which tries to describe human behavior more appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…6 All necessary background material about capacities and Choquet integration is given in Appendix A. 7 Since the Choquet integral is only positively homogeneous (Proposition A.6 (3)), the premium constraint cannot be written as R ě ş Y dν.…”
Section: Insurance Demand With Insurer Ambiguitymentioning
confidence: 99%
“…Young [46] and Bernard et al [6] examine the case where the insured is a Rank-Dependent Expected-Utility maximizer [37,45]. Doherty and Eeckhoudt [15] study the optimal level of deductible under Yaari's Dual Theory [45].…”
Section: Introductionmentioning
confidence: 99%
“…12 A number of papers have studied portfolio theory, risk-sharing and insurance contracting in the RDEU framework; see Bernard, He, Yan, and Zhou (2013) for a detailed review.…”
Section: Choquet Expected Utility Theorymentioning
confidence: 99%